Diatoms of Bagmati River, Kathmandu, Nepal - Rai, Shiva Kumar; Khadka, Sudip (Nepalese Journal of Biosciences, 2017)
This paper is an outcome of M.Sc. dissertation work carried out by second author during 2014 in Bagmati River, Kathmandu, Nepal. Diatom samples were collected by scraping stones with the toothbrush, squeezing macrophytes and sucking by dropper from three different sites (Mulkharka, Gokarna, Guheshwori-Pashupatinath) along the river during summer, rainy and winter seasons and studied thoroughly in the Phycology Researh Laboratory, Department of Botany, Post Graduate Campus, Biratnagar. A total 48 diatom taxa belonging to 25 genera and 12 families were enumerated. Among them, 20 diatoms were reported first time from Nepal viz., Fragilaria vaucheriae, Achnanthes inflata, Planothidium lanceolatum, Eunotia botuliformis, Gyrosigma scalproides, Stauroneis smithii, Sellaphora capitata, Neidium ampliatum, Navicula escambia, Pinnularia cf divergens, P. grunowii, Gomphonema acidoclinatum, G. gandhii, G. pseudoaugur, G. rhombicum, Cymbella turgidula, Encyonema hustedtii, E. ventricosum, Epithemia adnata, and Surirella angusta. Further extensive studies are essential to understand more about new and interesting diatoms of this river.